Oxidation of Methionine by Sodium N-Chlorobenzene Sulphonamide in Hydrochloric Acid Medium: A Kinetic Study - Ananda, S.; Mallamma; Rangaswamy (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of DL-methionine (Met) in the presence of HCl by sodium N-chlorobenzene sulphonamide (chloramine-B or CAB) have been performed at 30°C. The rate shows a first order dependence each on [CAB] and [H+] and zero order dependence on [Met]. The variation of the ionic strength, dielectric constant of the medium and addition of chloride ion and the reaction product of CAB (benzene sulphonamide) do not have any significant effect on the reaction rate. The activation parameters have been evaluated.